Hubungan Adopsi Ifrs Psak No.16 (Revisi 2007) Dengan Discretionary Accruals Sebagai Alat Manajemen Laba Serta Pengaruhnya Terhadap Nilai Perusahaan - son, andi (UNIVERSITAS NEGERI SURABAYA, 2017)
AbstractThe purpose of this study to determine the effect of earnings management on firm performance. Earnings management proxy by discretionary accruals, firm performance meausured by Tobins’s Q. The study used secondary data listed in Indonesia Stock Exchange on manufacturing company period 2013 – 2015 and result sampel 33 firm-years. Data analysis with regression. The result show earnings management negative effect on firm performance, and supported Huang et. al. (2009).